약물 복용력이 없는 주의력결핍 과잉행동장애 남아의 시각적 Go/NoGo 과제 수행결과 및 수행시의 사건관련전위 - 김건우(Kyuwoo Kim); 이중선(Jungsun Lee); 박수빈(Subin Park); 홍진표(Jin Pyo Hong); 김성윤(Seong Yoon Kim); 유한익(Hanik K. Yoo) (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2009)
Objectives: The purpose of this study was to examine the performance and electrophysiological characteristics of drug-naive children with attention-deficit/hyperactivity disorder(ADHD) during the Go/NoGo task. Methods: Twenty-three boys with ADHD and 18 age-matched normal boys were recruited at a child psychiatric outpatient clinic in Seoul. All subjects were assessed by the Kiddie Schedules for Affective Disorders and Schizophrenia Present and Lifetime version. The investigator also assessed all subjects using the ADHD Rating Scale-IV(ADHDRS). Event-related potentials were recorded from 8 scalp electrodes during the visual Go/NoGo task. Results: Children with ADHD showed a larger mean of standard deviation of response time during the Go/NoGo task than normal children. The temporal N200 and P300 amplitudes were larger in children with ADHD relative to controls. The parietal N200 and P300 latencies were more prolonged in children with ADHD compared to normal controls. Conclusion: These results suggest that psychotropic-naive children with ADHD may have more variable performance ability, more difficulty in discriminating visual stimuli, and slower information processing speed than their normal age-matched counterparts.